Uncertainty of Images of the Future and Peculiarities of Modern Social Thinking - Viktor Shcherbyna (Ukrainian Policymaker)
The article is devoted to the consideration of the problem of forming images of the future in the modern socio-historical situation. In posing the problem, the author proceeds from the fact that crisis, uncertainty and instability of social processes and institutions give rise to uncertainty of images of the future. The absence of certain images of the future in humanitarian discourse contributes to the development of social anomie, mass deprivation and the development of an existential vacuum.The author believes that images of the future are formed on the basis of a certain type of social thinking, in which static and dynamic aspects can be distinguished, allowing one to see social reality in its spatial and temporal characteristics. The dynamics of changes in social reality appear in images of the past, present and future. In society, many types of social thinking are simultaneously formed under the influence of historical events. Based on this, a hypothesis has been formed that images of the future differ depending on the type of cultural structure on the basis of which social thinking is formed. It is concluded that the image of the future is a necessary element of social reality. This is a means of social hegemony, reflecting the average expectations of individual social groups and society as a whole, in a specific historical and sociocultural situation. The author states that in social philosophy and theoretical sociology, there has been a new «ontological turn» – the desire to think about reality as it exists outside the established ways of social thinking. It is concluded that the image of the future in the conditions of social reality, which is qualitatively changing, can be developed on the basis of dialectical thinking.